Mathematical representation ability of students’ grade X in mathematics learning on problem based learning - Utami, Palupi Retno; Junaedi, Iwan; Hidayah, Isti (Department of Mathematics, Universitas Negeri Semarang, 2018)
The purposes of this study were to obtain a description of learning quality on problem based learning to improve the mathematical representation ability of students grade X and to get description about mathematical representation ability of students grade X in mathematics learning on problem based learning. this study used qualitative method. Qualitative methods is procedure of study that produce descriptive data in the words or oral from people and behaviour that can be observed. The study was conducted at SMA 1 Bumiayu with the subject of this study is the students of X MIPA 6. The subject of this study are students and teacher. The students that chosen as a subject of the study were selected as many as 6 person.they are 2 person from upper group, 2 person from medium group and 2 person from lower group. Based on the study thet has been done, the result shows that (1) the quality of mathematical learning on problem based learning in good category, (2) mathematical representation ability of students in each groups is different. Words representation ability and mathematical expressions ability shows a uniform pattern. On the visual representation ability shows diverse pattern.